2021
DOI: 10.1111/cpr.13139
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of circular RNAs in neuropathic pain

Abstract: Neuropathic pain is a major type of chronic pain caused by the disease or injury of the somatosensory nervous system. It afflicts about 10% of the general population with a significant proportion of patients’ refractory to conventional medical treatment. This highlights the importance of a better understanding of the molecular pathogenesis of neuropathic pain so as to drive the development of novel mechanism‐driven therapy. Circular RNAs (circRNAs) are a type of non‐coding, regulatory RNAs that exhibit tissue‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“… 28 , 62 Recently, emerging studies found that circRNAs play important roles in developing and maintaining neuropathic pain. 13 , 63 For instance, Zhang et al found 22 DE circRNAs in rat spinal cord on days 7 and 14 following SNL. And they proved that the up-regulated CircAnks1a in the spinal cord of rats contributes to the hypersensitivity in the paw induced by SNL injury.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 62 Recently, emerging studies found that circRNAs play important roles in developing and maintaining neuropathic pain. 13 , 63 For instance, Zhang et al found 22 DE circRNAs in rat spinal cord on days 7 and 14 following SNL. And they proved that the up-regulated CircAnks1a in the spinal cord of rats contributes to the hypersensitivity in the paw induced by SNL injury.…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs have also been involved in neuropathic pain (reviewed elsewhere: [ 94 ]). Recent preclinical studies using the CCI model in rats have identified imbalances in different circRNAs.…”
Section: Non-coding Rnas and Painmentioning
confidence: 99%
“… * Note there are other ncRNA involved in nociceptive processing, which are not included in this table as have been covered in recent reviews, see [ 91 , 92 , 93 , 94 , 95 ]. …”
Section: Figurementioning
confidence: 99%
“…Neuropathic pain results from damage or disease to the somatosensory nervous system, characterized by allodynia, hyperalgesia, and spontaneous pain ( Xu et al, 2021 ). At the same time, the transmission of long-term nociceptive signals induces plasticity changes in the structure and function of some brain regions such as the medial prefrontal cortex (mPFC) ( Mecca et al, 2021 ), ACC ( Smith et al, 2021 ), amygdala ( Murugappan et al, 2021 ), and hippocampus ( Toledo et al, 2021 ), which are also involved in the regulation of emotion and cognitive functions, so that nociceptive signals not only include pain components but also cover emotion-related components in the brain ( De Ridder et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%